Impact of Reactor Operation on Success of Struvite Precipitation from Synthetic Liquors - Le Corre, Kristell S.; Valsami-Jones, Eugenia; Hobbs, Phil; Parsons, Simon A. (Taylor & Francis, 2007)
A pilot scale reactor was designed and developed to study struvite crystallisation principles. The present work focuses on the possible impact of the reactor's operating parameters on struvite characteristics, and evaluates the performances of the process in removing phosphorus. Struvite precipitation from synthetic liquors was investigated under various situations including: pH, magnesium dosing, addition of foreign ions such as calcium and increasing retention time. Small variations of a these parameters were found to have significant effects on struivite crystal characteristics and/or production. For instance, an increase of pH from 10.0 to 10.5 favoured the formation of Mg3(PO4)2.22H2O rather than struvite. For molar ratios Ca:Mg above 1:1, calcium ions competed with magnesium to form an amorphous calcium phosphate, hence inhibiting struvite formation. With regards to crystal growth, the process showed some limitations. Indeed, large amounts ot fines were produced, and crystal rarely grew over 100 pm under optimum conditions, Based on those observations, zeta-potential measurements of struvite crystals were investigated. Results revealed highly negative zeta-potential values for all experiments, indicating that this may be a limitation to struvite tendency for agglomeration.